Binder-Free Immobilization of Photocatalyst on Membrane Surface for Efficient Photocatalytic H2O2 Production and Water Decontamination - Hu, Zhen‑Yu; Liu, Tian; Yang, Yu‑Ru; An, Alicia Kyoungjin; Liew, Kim Meow; Li, Wen‑Wei (Nano-Micro Letters, 2025)
In photocatalytic water treatment processes, the particulate photocatalysts are typically immobilized on membrane, through either chemical/physical loading onto the surface or directly embedding in the membrane matrix. However, these immobilization strategies inevitably compromise the interfacial mass diffusion and cause activity decline relative to the suspended catalyst. Here, we propose a binder-free surface immobilization strategy for fabrication of high-activity photocatalytic membrane. Through a simple dimethylformamide (DMF) treatment, the nanofibers of polyvinylidene fluoride membrane were softened and stretched, creating enlarged micropores to efficiently capture the photocatalyst. Subsequently, the nanofibers underwent shrinking during DMF evaporation, thus firmly strapping the photocatalyst microparticles on the membrane surface. This surface self-bounded photocatalytic membrane, with firmly bounded yet highly exposed photocatalyst, exhibited 4.2-fold higher efficiency in hydrogen peroxide (H2O2) photosynthesis than the matrix-embedded control, due to improved O2 accessibility and H2O2 diffusion. It even outperformed the suspension photocatalytic system attributed to alleviated H2O2 decomposition at the hydrophobic surface. When adopted for UV-based water treatment, the photocatalytic system exhibited tenfold faster micropollutants photodegradation than the catalyst-free control and demonstrated superior robustness for treating contaminated tap water, lake water and secondary wastewater effluent. This immobilization strategy can also be extended to the fabrication of other photocatalytic membranes with diverse catalyst types and membrane substrate. Overall, our work opens a facile avenue for fabrication of high-performance photocatalytic membranes, which may benefit advanced oxidation water purification application and beyond. Highlights: 1 Polyvinylidene fluoride nanofibers were treated by dimethylformamide to create micropores on membrane surface. 2 Photocatalysts were firmly bounded by nanofibers during stretching and shrinking. 3 Particulate catalysts were fixed yet high exposed on the membrane surface. 4 Surface self-bounded photocatalytic membrane exhibited tenfold higher decontamination activity than embedded catalyst.